Jogo sério para aprendizagem da instabilidade de vertentes - Gonçalo Ferreira Araújo (2013)
Serious games have been receiving a lot of interest in the recent years and have been massively used for educational, military and business purposes. One of the positive sides of serious games is the fact of being tools that allow the creation of an environment where players are immersed in a playful activity, and are much more open to the reception of new knowledge. Through serious games, players are more likely to retain information for a wider period of time. Therefore, this dissertation will use serious games to teach the problem of terrain instability and slope movements. The solution found was to make a serious game in Unity, which aims to teach some Geography terms, and slope instability terms in particular, through real steps that are made by geographers. Therefore players learn about terrains who may be bound to slope movements, at the same time that they accomplish a playful activity.